2023
DOI: 10.1111/1749-4877.12710
|View full text |Cite
|
Sign up to set email alerts
|

Altitude‐dependent metabolite biomarkers reveal the mechanism of plateau pika adaptation to high altitudes

Abstract: The harsh environment in the Tibetan plateau, the highest place in the world, poses thermoregulatory challenges and hypoxic stress to animals. The impacts of plateau environment on animal physiology and reproduction include external factors such as strong ultraviolet radiation and low temperature, and internal factors such as animal metabolites and gut microbiota. However, it remains unclear how plateau pika adapt to high altitudes through the combination of serum metabolites and gut microbiota. To this end, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In OPLS-DA model, R 2 X represented the cumulative explanatory rate of the model in the X -axis direction, and Q 2 represented the cumulative prediction rate of the model when modeling the multivariate statistical analysis. In theory, when the values of R 2 X and Q 2 were closer to 1, indicating a better model, and it was acceptable when R 2 X and Q 2 were higher than 0.4 . In Figure , the control group and the swainsonine-treated groups were distributed on both sides of the y -axis, and the R 2 X values and Q 2 values were greater than 0.4, indicating that their metabolites in the serum and liver were significantly different after swainsonine treatment compared to the control.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In OPLS-DA model, R 2 X represented the cumulative explanatory rate of the model in the X -axis direction, and Q 2 represented the cumulative prediction rate of the model when modeling the multivariate statistical analysis. In theory, when the values of R 2 X and Q 2 were closer to 1, indicating a better model, and it was acceptable when R 2 X and Q 2 were higher than 0.4 . In Figure , the control group and the swainsonine-treated groups were distributed on both sides of the y -axis, and the R 2 X values and Q 2 values were greater than 0.4, indicating that their metabolites in the serum and liver were significantly different after swainsonine treatment compared to the control.…”
Section: Discussionmentioning
confidence: 94%
“…In theory, when the values of R 2 X and Q 2 were closer to 1, indicating a better model, and it was acceptable when R 2 X and Q 2 were higher than 0.4. 24 In Figure 1, the control group and the swainsonine-treated groups were distributed on both sides of the y-axis, and the R 2 X values and Q 2 values were greater than 0.4, indicating that their metabolites in the serum and liver were significantly different after swainsonine treatment compared to the control. The permutation tests further verified the validity of the models (Figure S3A−F).…”
Section: Discussionmentioning
confidence: 98%
“…Mice with metabolic syndrome (Mets) have abnormal testicular spermatogenesis due to impaired vitamin A absorption in the intestine, which may be associated with the significantly reduced abundance of Ruminococcaceae (NK4A214group) (Zhang et al, 2022 ). As an androgen found in epididymal cells, dihydrotestosterone (DHT) regulates sperm maturation (Robaire and Henderson, 2006 ), and a large-scale animal study suggested that an abundance of Ruminococcaceae was positively correlated with DHT (Chen et al, 2023 ). Regulation of the gut microbiota to improve the symptoms of drug-induced male infertility was demonstrated by several studies (Zhao et al, 2020b ; Sun et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The samples collected in August and January represent warm and cold seasons, respectively. According to the physiological and reproductive characteristic of plateau pikas ( 73 76 ), we defined the samples collected over altitude 3,900 m as high altitudinal samples, while the samples collected below 3,900 m were defined as low altitudinal samples. On average, 10 individuals were randomly captured at each sampling site.…”
Section: Methodsmentioning
confidence: 99%